2004
DOI: 10.1348/0144666042038015
|View full text |Cite
|
Sign up to set email alerts
|

False consensus in social context: Differential projection and perceived social distance

Abstract: The study implicates the notion of perceived social distance as an explanation of why ingroup false consensus exceeds outgroup false consensus. Whilst previous demonstrations are best understood from social identity perspectives, the findings reported here suggest that self-group as well as inter-group comparisons can underlie such effects. In particular, perceived social distance was shown to mediate the effect of social categorisation: ingroup false consensus was greater because more social distance was perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 23 publications
0
34
1
2
Order By: Relevance
“…The few examples of negative social projection were found among people who both strongly identified with their ingroup and perceived strong conflict with the outgroup (Riketta, 2005), among members of a low status group with regards to the perception of the attributes of the high status group (Holtz & Nihiser, 2008), and among people who perceive high social distance between their ingroup and the outgroup (Jones, 2004).…”
Section: Studymentioning
confidence: 99%
“…The few examples of negative social projection were found among people who both strongly identified with their ingroup and perceived strong conflict with the outgroup (Riketta, 2005), among members of a low status group with regards to the perception of the attributes of the high status group (Holtz & Nihiser, 2008), and among people who perceive high social distance between their ingroup and the outgroup (Jones, 2004).…”
Section: Studymentioning
confidence: 99%
“…attitudes, traits) ascribed to the self and attributes ascribed to natural groups (for reviews, see Krueger, 1998Krueger, , 2000Mullen et al, 1985; for more recent research, see, e.g. Ames, 2004a,b;Clement & Krueger, 2002;Jones, 2004;Riketta, 2005). Thus, social projection seems to be common (Krueger, 1998(Krueger, , 2000.…”
Section: Social Projection and The Postulated Role Of Perceived Intermentioning
confidence: 99%
“…Two other lines of research on social projection dealt with constructs that are related to (yet distinct from) perceived intergroup relationship (Ames, 2004a,b;Jones, 2004). Ames postulated and found in experimental and correlational studies that perceived global similarity of self to in-and outgroups leads to stronger perceived similarity between self and these groups on habits and attitudes.…”
Section: Previous Fi Ndings On the Role Of Perceived Intergroup Relatmentioning
confidence: 99%
“…While the FCE has traditionally examined how the generalized other is misperceived, recent research has found this effect with specific others, such as peers (Prinstein and Wang 2005). Indeed, FCE effects tend to be stronger when the ''other'' is perceived to be similar (Sherman et al 1985) or less socially distant to the individual (Jones 2004).…”
Section: Perception Of Partner Hiv-specific Risk Behaviorsmentioning
confidence: 99%